Enhancing Critical Thinking Through Coastal Culture-Based Differentiated Science Learning - Fitri April Yanti; Rendy Wikrama Wardana; Noorzana Khamis (Jurnal Inovasi Pendidikan IPA, 2025)
The purpose of this study was to enhance critical thinking skills through the implementation of coastal culture-based differentiated science learning. The research was conducted from August to November 2024 using a quasi-experimental nonequivalent control group design at  State Junior High School 2 Bengkulu, Indonesia. The sample consisted of three eighth-grade classes: experimental group 1 (8A), experimental group 2 (8B), and the control group (8C), selected through purposive sampling. Students’ critical thinking skills were assessed using a validated and reliable test instrument (r = .89). Data were analyzed with one-way ANOVA, which revealed significant differences among groups (p < .001). The average N-gain score of critical thinking skills in experimental group 1 (.40, medium category) was higher than that of experimental group 2 (.20, low category) and the control group (.009, low category). Based on the hypothesis testing, it can be concluded that coastal culture-based differentiated science learning has a significant effect on students’ critical thinking skills (p < .001). These findings confirm that culturally contextualized differentiated learning significantly enhances critical thinking. Theoretically, this model contributes to science pedagogy by integrating cultural relevance to support effective, innovative instruction